2019
DOI: 10.1016/j.jalz.2019.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Association between enrollment factors and incident cognitive impairment in Blacks and Whites: Data from the Alzheimer's Disease Center

Abstract: Introduction: We examined the influence of enrollment factors demonstrated to differ by race on incident mild cognitive impairment and dementia using Alzheimer's Disease Center data. Methods: Differences in rates of incident impairment between non-Latino Whites and Blacks (n 5 12,242) were examined with age-at-progression survival models. Models included race, sex, education, source of recruitment, health factors, and family history of dementia. Results: No significant race differences in progression were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 49 publications
1
74
0
Order By: Relevance
“…Without critical developments in operationalization and measurement of engagement and recruitment activities, and deliberate intent to include underrepresented populations in research studies, we risk misunderstanding—or worse, exacerbating—existing disparities in AD. Indeed, recent work by Gleason and colleagues [ 107 ] demonstrated that recruitment bias confounds with racial identity in determining AD risk in large datasets such as the National Alzheimer’s Clinical Consortium repository, suggesting that our largest, most crucial resources already inaccurately estimate racial disparities in AD. Inclusion of underrepresented populations in AD research, if only for the sake of accurate estimation of dementia risk, is a promising frontier that requires advanced understanding of effective recruitment and engagement mechanisms.…”
Section: Call To Action Aimed At Improving Enrollment In Ad Clinical Trialsmentioning
confidence: 99%
“…Without critical developments in operationalization and measurement of engagement and recruitment activities, and deliberate intent to include underrepresented populations in research studies, we risk misunderstanding—or worse, exacerbating—existing disparities in AD. Indeed, recent work by Gleason and colleagues [ 107 ] demonstrated that recruitment bias confounds with racial identity in determining AD risk in large datasets such as the National Alzheimer’s Clinical Consortium repository, suggesting that our largest, most crucial resources already inaccurately estimate racial disparities in AD. Inclusion of underrepresented populations in AD research, if only for the sake of accurate estimation of dementia risk, is a promising frontier that requires advanced understanding of effective recruitment and engagement mechanisms.…”
Section: Call To Action Aimed At Improving Enrollment In Ad Clinical Trialsmentioning
confidence: 99%
“…Most of the neuropathological studies discussed here enrolled African American individuals with dementia from a clinic setting; however, the recruitment of study participants, particularly African American individuals, from a specialty memory clinic is known to be prone to selection bias 6 , 49 . For example, because of fractured health-care relationships, mistrust and misconceptions about AD being a ‘normal part of ageing’ 60 , African American individuals are more likely to present to medical attention with behavioural problems, such as hallucinations, agitation and sleep disorders, than for memory problems 6 .…”
Section: Understanding Racial Differencesmentioning
confidence: 99%
“…Such efforts will be essential for achieving successful recruitment and high rates of follow-up, and for encouraging participants to consent to invasive procedures such as, organ donation, lumbar puncture and PET that are often included in AD research. The recruitment of diverse samples that are representative of the community should be the goal of such efforts; differential selection into a study by race or ethnicity could give rise to selection bias and exacerbate disparities 49 . Thus the study recruitment pipelines for African American individuals and white individuals must be intentionally designed so that they do not create an intractable selection bias.…”
Section: Strategies To Move Forwardmentioning
confidence: 99%
“…This under-enrollment leads to conclusions about disease risk factors and processes without all the necessary data because the studies are not representative of all people and all life experiences. 3…”
Section: Introductionmentioning
confidence: 99%